2020
DOI: 10.1155/2020/8890477
|View full text |Cite
|
Sign up to set email alerts
|

Channel and Feature Selection for a Motor Imagery-Based BCI System Using Multilevel Particle Swarm Optimization

Abstract: Brain-computer interface (BCI) is a communication and control system linking the human brain and computers or other electronic devices. However, irrelevant channels and misleading features unrelated to tasks limit classification performance. To address these problems, we propose an efficient signal processing framework based on particle swarm optimization (PSO) for channel and feature selection, channel selection, and feature selection. Modified Stockwell transforms were used for a feature extraction, and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…As an efficient way to solve NP-compete problems, heuristic-searching-based methods have been adopted to solve channel selection problems successfully. Some commonly used heuristic algorithms are genetic algorithms (Moctezuma and Molinas, 2020 ), particle swarm optimization (Qi et al, 2020 ), simulated annealing (Yang, 2020 ), ant colony optimization (Miao et al, 2020 ), differential evolution (Hajizamani et al, 2020 ), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…As an efficient way to solve NP-compete problems, heuristic-searching-based methods have been adopted to solve channel selection problems successfully. Some commonly used heuristic algorithms are genetic algorithms (Moctezuma and Molinas, 2020 ), particle swarm optimization (Qi et al, 2020 ), simulated annealing (Yang, 2020 ), ant colony optimization (Miao et al, 2020 ), differential evolution (Hajizamani et al, 2020 ), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature [31,32], selecting the right activity channels can help to improve the categorization ability. In addition, several studies have demonstrated the effectiveness of feature selection for BCIs [33][34][35]. Feature selection helps to reduce the dimensionality of the dataset, increase processing efficiency, and improve the classification accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a means that combining L1-MCCA with particle swarm optimization (PSO) [36][37][38] optimized SVM was proposed to improve the accuracy of SSVEP based BCI. SSVEP data of 15 participants were recorded to investigate the reliability and the performances of the L1-MCCA-PSO-SVM method.…”
Section: Introductionmentioning
confidence: 99%